Evaluation of Black Rice under Different Fertilizer Doses in Western Terai, Nepal - Khadka, Ram Bahadur (Agronomy Journal of Nepal, 2016)
The black rice varieties are considered to have multiplier benefits in human health due to the presence of different antioxidants. An experiment was conducted at RARS, Khajura during rainy season of 2014 to evaluate the response of black rice with different doses of fertilizers and to document the basic phonological characters. It was found to be of short duration, low productive and non-responsive towards the fertilizer doses. Due to health benefiting qualities, the market price could easily compensate the low productivity and be of high commercial value in farming communities. However, more detail studies required on agronomy, protection, quality and breeding aspects before going to commercialization.Agronomy Journal of Nepal (Agron JN), Vol.4, Page: 136-141, 2016